Adhesion and Polarity protein distribution-regulates hexagon dominated plasma membrane organization in Drosophila blastoderm embryos. - Dey, B.; Mitra, D.; Das, T.; Sherlekar, A.; Balaji, R.; Rikhy, R. (Genetics, 2023)
Epithelial cells contain polarity complexes on the lateral membrane and are organized in a hexagon-dominated polygonal array. The mechanisms regulating the organization of polygonal architecture in metazoan embryogenesis are not completely understood. Drosophila embryogenesis enables mechanistic analysis of epithelial polarity formation and its impact on polygonal organization. The plasma membrane (PM) of syncytial Drosophila blastoderm embryos is organized as a polygonal array with pseudocleavage furrow formation during the almost synchronous cortical division cycles. We find that polygonal (PM) organization arises in the metaphase (MP) of division cycle 11, and hexagon dominance occurs with an increase in furrow length in the metaphase of cycle 12. There is a decrease in cell shape index in metaphase from cycles 11 to 13. This coincides with Drosophila E-cad (DE-cadherin) and Bazooka enrichment at the edges and the septin, Peanut at the vertices of the furrow. We further assess the role of polarity and adhesion proteins in pseudocleavage furrow formation and its organization as a polygonal array. We find that DE-cadherin depletion leads to decreased furrow length, loss of hexagon dominance, and increased cell shape index. Bazooka and Peanut depletion lead to decreased furrow length, delay in onset of hexagon dominance from cycle 12 to 13, and increased cell shape index. Hexagon dominance occurs with an increase in furrow length in cycle 13 and increased DE-cadherin, possibly due to the inhibition of endocytosis. We conclude that polarity protein recruitment and regulation of endocytic pathways enable pseudocleavage furrow stability and the formation of a hexagon-dominated polygon array.